2012
DOI: 10.1093/chemse/bjr120
|View full text |Cite
|
Sign up to set email alerts
|

Slow Breathing and Emotions Associated with Odor-Induced Autobiographical Memories

Abstract: An important feature of olfactory perception is its dependence on respiratory activity. By inspiration, olfactory information ascends directly to olfactory-related limbic structures. Therefore, every breath with odor molecules activates these limbic areas associated with emotional experience and memory retrieval. We tested whether odors associated with autobiographical memories can trigger pleasant emotional experiences and whether respiration changes during stimulation with these odors. During presentation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 27 publications
2
53
1
Order By: Relevance
“…In other words, deep breathing and pleasantness mutually affect each other. Pleasant olfactory mental imagery contributes to increased feelings of pleasantness and comfortableness, leading to deep breathing and reduced respiratory rate (39). The second hypothesis suggests that there is a deep synchronization between the brain's slow-wave (alpha waves) across the entire cortical mantle and slow and deep breathing pattern during sleep.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In other words, deep breathing and pleasantness mutually affect each other. Pleasant olfactory mental imagery contributes to increased feelings of pleasantness and comfortableness, leading to deep breathing and reduced respiratory rate (39). The second hypothesis suggests that there is a deep synchronization between the brain's slow-wave (alpha waves) across the entire cortical mantle and slow and deep breathing pattern during sleep.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, it was shown that olfactory mental imagery of pleasant odors can increase respiratory amplitude and respiratory minute volume only by increasing tidal volume and improving the breathing pattern without any changes in the respiratory rate, resulting in an improvement in the respiratory function (37). In addition, a study by Masaoka et al indicated that odors associated with autobiographical pleasant memory can prolong inspiratory and expiratory times, particularly expiratory, resulting in a deep and slow breathing pattern (39). Prolonged expiration triggered by olfactory imagery (39) increases intra-thoracic pressure (54) which pushes more blood into the heart with a subsequent increase in stroke volume.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations